2020
DOI: 10.1017/s1355617720000405
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment and Prediction of Prospective Memory after Stroke

Abstract: Objective: Prospective memory (PM) is the memory used when intentions are to be carried out in the future. Little research has been conducted examining PM after stroke. This study aimed to determine if PM is impaired after stroke through comparison of individuals with stroke to healthy controls. Additionally, it aimed to explore the predictors of PM performance post-stroke. Method: Twenty-eight individuals with stroke and 27 neurologically healthy controls completed the Cambridge Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…This is in agreement with some of the previous studies (Barr, 2011) but not others (Man et al, 2015). It is also important to note that the current stroke sample, when tested using a psychometrically valid clinical measure (Cambridge Prospective Memory Test; CAMPROMPT;Wilson et al, 2005) as part of the larger study, performed significantly lower than controls, suggesting the presence of PM impairment (Hogan, Cornwell, Fleming, & Shum, 2020). These findings are consistent with the selfreport of more PM failures when compared to controls in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with some of the previous studies (Barr, 2011) but not others (Man et al, 2015). It is also important to note that the current stroke sample, when tested using a psychometrically valid clinical measure (Cambridge Prospective Memory Test; CAMPROMPT;Wilson et al, 2005) as part of the larger study, performed significantly lower than controls, suggesting the presence of PM impairment (Hogan, Cornwell, Fleming, & Shum, 2020). These findings are consistent with the selfreport of more PM failures when compared to controls in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with stroke showed impairments in time-based PM compared to controls but only on the LDPMT. This is in line with previous research that has found that individuals with stroke have impaired PM compared to healthy controls (Barr, 2011;Brooks et al, 2004;Hogan et al, 2016;Man, Chan, et al, 2015), particularly time-based PM (Cheng et al, 2010;Hoganet al, 2021;Hogan, Cornwell, Fleming, & Shum., 2020;Kant et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Hypothesis one, that individuals with stroke would perform poorer than controls on time-and event-based PM on all PM measures, was partly supported. Consistent with previous research (Barr 2011;Hogan et al 2020;Man et al 2015b) individuals with stroke performed significantly poorer than controls on both event-and time-based PM on the CAMPROMPT. On the VRPMST and LDPMT individuals with stroke performed significantly poorer than controls on time-based PM.…”
Section: Discussionsupporting
confidence: 90%